2007
DOI: 10.1152/ajpgi.00452.2006
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of intragastric acid stability of a fat emulsion meal delays gastric emptying and increases cholecystokinin release and gallbladder contraction

Abstract: RC. Enhancement of intragastric acid stability of a fat emulsion meal delays gastric emptying and increases cholecystokinin release and gallbladder contraction. Am J Physiol Gastrointest Liver Physiol 292: G1607-G1613, 2007. First published March 1, 2007; doi:10.1152/ajpgi.00452.2006.-Preprocessed fatty foods often contain calories added as a fat emulsion stabilized by emulsifiers. Emulsion stability in the acidic gastric environment can readily be manipulated by altering emulsifier chemistry. We tested the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
129
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(135 citation statements)
references
References 45 publications
5
129
0
Order By: Relevance
“…Furthermore, the shape of emptying curve was exponential for unstable meal instead of linear for stable emulsion. More CCK was released after ingestion of the acid stable meal (1095 ± 244 pmole min/L) than after acid unstable meal (531 ± 111 pmole min/L), inducing a greater gallbladder contraction and decreasing postprandial appetite (Marciani et al, 2007). In another study, authors confirmed that acid-stable meals quitted more rapidly the stomach than acid-unstable meals and once in the duodenum lipids would be hydrolyzed more rapidly because of the higher surface area available for lipase/colipase complex (Marciani et al, 2009).…”
Section: Faʃy Acids 2-mono-acyl Glycerolsmentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, the shape of emptying curve was exponential for unstable meal instead of linear for stable emulsion. More CCK was released after ingestion of the acid stable meal (1095 ± 244 pmole min/L) than after acid unstable meal (531 ± 111 pmole min/L), inducing a greater gallbladder contraction and decreasing postprandial appetite (Marciani et al, 2007). In another study, authors confirmed that acid-stable meals quitted more rapidly the stomach than acid-unstable meals and once in the duodenum lipids would be hydrolyzed more rapidly because of the higher surface area available for lipase/colipase complex (Marciani et al, 2009).…”
Section: Faʃy Acids 2-mono-acyl Glycerolsmentioning
confidence: 95%
“…The choice of the surfactant is a key to control for the stability of an emulsion in the gastric environment. For example Tween 60 (E491, polyethoxy ethylene sorbitan monostearate) or Span 80 (E494, sorbitan monooleate) can be used to produce respectively acid-stable or unstable emulsions (Marciani et al, 2007) with similar droplet size (3.6 mm). Those emulsions were incorporated into a complete meal (500 ml, 675 kcal, 50 g lipids) and 5 h after their ingestion, subjects ingested 500 ml of a rehydrated vegetable soup (460 kcal, 12.5 g fat).…”
Section: Faʃy Acids 2-mono-acyl Glycerolsmentioning
confidence: 99%
“…A sustained reduction in daily calorie consumption could prevent or reduce this long term weight gain in a large proportion of the population, and thus to reduce the incidence of obesity and associated health problems. Fatty foods have high-energy density and palatability but exert a relatively weak effect on satiation (compared calorie per calorie with protein and carbohydrate foods), which may encourage calorie over-consumption (Marciani et al, 2007). Lowering energy density of foods can decrease energy intake independent of macronutrient content and palatability.…”
Section: Food-related Diseases Focused On Obesitymentioning
confidence: 99%
“…Signifi cant efforts have been made during the last decade to better understand the overall functioning of the human stomach and to develop a new generation of in vitro models of enhanced biochemical and mechanical relevance (Boulby et al 1999 ;Faas et al 2002 ;Kunz et al 2005 ;Goetze et al 2007Goetze et al , 2009Kwiatek et al 2006 ;Marciani et al 2001aMarciani et al , 2007Marciani et al , 2012Marciani 2011 ;Schwizer et al 2002Schwizer et al , 2006Steingoetter et al 2005 ;Treier et al 2006 ;Mackie et al 2013 ). More notably among those models are the TNO and DGM systems discussed in the previous sections.…”
mentioning
confidence: 99%